ANALYSIS THE CONDITION OF THE RUNWAY PAVEMENT UMBU MEHANG KUNDA AIRPORT WAINGAPU – NTT USING THE PAVEMENT CONDITION INDEX (PCI) METHOD - Djulia Maharani, Nandita; Fatimah, Siti; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Transportation is very much needed in an effort to much needed for developing an advanced country, one of the transportation that is very influential is air transportation, Umbu Mehang Kunda Waingapu Airport is one of the accesses to air transportation in East Sumba Regency, East Nusa Tenggara. This airport has a runway dimension of 2000 x 30 m with PCN 48 F/C/X/T. Every year the growth of aircraft and passenger movements has always increased. This often causes the runway pavement structure to be damage prematurely, besides that natural factors also have an effect. Runway damage can be assessed using the Pavement Condition Index (PCI) method. In analyzing the condition of the runway pavement using the Pavement Condition Index (PCI) method, a visual inspection of the runway surface at Umbu Mehang Kunda Waingapu Airport was carried out. Distribution of samples and calculations based on the ASTM document. The repair method is regulated in KP 94 of 2015 concerning Operational Technical Guidelines for Civil Aviation Safety Regulation. The results of the analysis carried out on the runway at Umbu Mehang Kunda Waingapu Airport showed several types of damage, namely Raveling/ Weathering, Bleeding, and Depression with an average value obtained of 54 in sufficient condition. Therefore, the method of repair in accordance with KP 94 of 2015 regulations is Overlay and Patching